Rape Myth Acceptance in Contemporary Times: A Comparative Study of University Students in India and the United Kingdom - Barn, Ravinder (Journal of interpersonal violence, 2021)
Much of the literature on rape, victim blaming, and rape myth acceptance is focused on the United States, and there is a general dearth of such scholarly activity in other countries. This article offers insights on university students’ perspectives in two new country contexts—India and the United Kingdom. A total of 693 students contributed to the data collection for this study. Rape myth acceptance was fairly low for both countries, however, students in India were more likely to endorse rape myths. Several demographic characteristics were significant for rape myth acceptance in each country. This study makes an important contribution to the extant literature to address paucity of knowledge and promote understandings to help develop country-specific and appropriate policy, practice, and education and awareness programs. In particular, the study provides novel comparative findings on rape myth acceptance in new country contexts to help advance academic thinking in this area of work.